Vaccination rate and symptoms of long COVID among dental teams in Germany - Mksoud, Maria; Ittermann, Till; Holtfreter, Birte; Söhnel, Andreas; Söhnel, Carmen; Welk, Alexander; Paris, Sebastian; Melzow, Florentina Sophie; Wiegand, Annette; Kanzow, Philipp; Rau, Andrea; Kindler, Stefan; et al. (Scientific reports, 2025)
Although COVID-19 is no longer a global public health threat, its consequences persist, with long COVID affecting at least 10% of patients and manifesting in various organ systems. National and international health agencies promoted vaccination to enhance population immunity, prioritizing healthcare personnel due to their high occupational risk. In a previous study, we found that the risk of SARS-CoV-2 transmission among dental teams in Germany was not higher than in the general population. This follow-up investigation aims to assess the vaccination status and the prevalence and severity of long COVID symptoms among dental teams in Germany. As part of a follow-up investigation involving the original cohort, 267 team members from 186 German dental practices previously included in the initial study completed an online questionnaire. The questionnaire covered three topics: (1) vaccination status, (2) confirmed COVID-19 diagnosis, and (3) self-reported long COVID symptoms. One hundred and seventy-two dentists (64.4%), 74 dental assistants (27.7%) and 21 dental hygienists (7.9%) completed the questionnaire. In total, 245 participants (91.8%) were at least once vaccinated. A COVID-19 infection after January 1st 2021 was reported by 146 (54.7%) participants, of which 33 participants (22.6%) suffered from long COVID symptoms. Our results showed lower vaccination rates among dental auxiliary personnel compared to dentists (95.9% vs. 84.2%). Individuals with long COVID symptoms were more often dental assistants (48.5% vs. 29.2%) or dental hygienists (15.2% vs. 8.0%) than dentists (36.4% vs. 62.8%) compared to the group not reporting long COVID symptoms ( p = 0.025). In addition, it is unlikely that dental healthcare personnel are more prone to experiencing more severe symptoms compared to the general population. Vaccination against SARS-CoV-2 is likely to help against symptoms of long COVID.